Antagonistic potential of soil fungi as biocontrol agent against rice pathogens (Bangladesh Journal of Botany, 2024)
Antagonistic potential of six soil fungi viz., Aspergillus flavus Link., A. fumigatus Fresen., A. niger Tiegh., Penicillium sp., Trichoderma harzianum Refat. and T. viride Pers. against eight pathogenic fungi viz., Alternaria alternata (Fr.) Keissler, Curvularia lunata (Wakker) Boedijn, Drechslera oryzae Breda de Haan (Subramanian and Jain), Fusarium moniliforme Sheldon, F. solani (Mart.) Sacc. Microdochium oryzae (Hashloka and Yokogi) Sam. and Hal., Pestalotiopsis guepinii (Desm.) Stay. and Sarocladium oryzae (Sawada) W. Gams and D. Hawks of rice were evaluated. In colony interaction, the highest growth inhibition (88%) was observed owing to T. harzianum against Alternaria alternata.Volatile substances from soil fungi inhibited the  radial growth of the test pathogens which varied from 8.33 to 57.36%.The highest inhibition (57.36%) was found owing to T. harzianum against P. guepinii. The inhibition of mycelial growth of the test pathogens ranged from 29.05 to 64.5% owing to non volatile substances of the soil fungi. The highest mycelial growth inhibition was observed owing to T. harzianum against C. lunata. Trichoderma harzianum may be exploited commercially to control rice pathogens.Bangladesh J. Bot. 53(1): 101-108, 2024 (March)